THE CORPORAL MOVEMENT AND THE SPORTS: IT'S PERSONAL MEANING, SOCIAL AND CULTURAL AS REFLECTED OF THE SCIENCE OF THE CITIZEN (Fiep Bulletin - online, 2014)
The body informs the mind through sensorial organs, analyzing the harvested answers of the environment, modifying or reaffirming its intentions. Through the movement the man integrates the exterior data, which related and systemize evolution they originate the cortical process, thus organizing the mental life in function of the past and projects itself for front, in function of the future. It has different explanations about the education's influence in the process and it's related with the learning and intellectual development. The determination of its behavior is in summons related with the individual's structure; they are basically the guarantees of different behaviors. Different explanations regarding the influence of education in the human's discovery process and its relation with the learning and the intellectual development of the pertaining to school exist. New situations that take the pupils to exercise attitudes and become citizens, valuing the provoked beneficial transformations in the individual for the practical one of physical and porting activities, assays the interpersonal relations. These interactive aspects indicate the relevance of a practical environment where the activities have one educational meaning defined and in accordance with the objective of education to be reached. The body movements promoted by the sports and the physical activities favor to the psychic, physical and social development of the pupils; creating alternative in the schools for the acquisition of porting and recreational material, stimulating the relations of affectivity, breakthrough them for a critical and intense reflection how much to its evolvement with the school's environment. Practicing sports the child acquires psychomotor dexterities, psychics and the friendships that appear neutralize or canalize its trend to the instability and the aggressiveness.
Keywords: meaning; expression of the movement; anticipation of the action